PENGEMBANGAN MODEL PERMAINAN VOLI TENIS (VOTEN) - Ziskhan Asiqqin; Titis Nurina; Ahmad Alwi Nurudin (Universitas Negeri Medan, 2019)
Research objectives: (1) introduce and overcome the problem of limited facilities and infrastructure of playing tennis in schools; (2) to produce new sports games that are useful for the community, and for sports lovers. This study refers to the development model of Sugiyono, namely: (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) product revisions; (6) product trials; (7) product revisions; (8) trial use; (9) final product. The subjects of this study were the 12th grade volleyball extracurricular members of the MA Sakanikat Islam Parakansalak District of Sukabumi, totaling 12 people and the volleyball extracurricular participants in class XI of SMA Negeri 2 Sukabumi, totaling 14 people. The data collection technique used is descriptive percentage. While the data in the form of suggestions and reasons for choosing answers were analyzed using qualitative analysis techniques. From the results of this development research the presentation was obtained when the small group trial 85% with Very Eligible criteria and the results of the percentage of large-scale trials 92.5% with Very Eligible criteria.